Polyherbal Transdermal Patches and Evaluation for Rheumatoid Arthritis (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disorder characterized by persistent synovial inflammation, joint pain, stiffness, swelling, and progressive cartilage and bone destruction, resulting in impaired quality of life. Conventional oral anti-inflammatory drugs often produce adverse effects such as gastrointestinal irritation, frequent dosing, and reduced patient compliance. Transdermal drug delivery offers a promising alternative by providing sustained drug release, improved bioavailability, avoidance of first-pass metabolism, and enhanced patient convenience. The present study aims to formulate and evaluate polyherbal transdermal patches for the management of rheumatoid arthritis using medicinal plants possessing anti-inflammatory and antioxidant properties. Herbal extracts such as Vitex negundo, Boswellia serrata, and Curcuma longa will be incorporated into a suitable polymeric matrix prepared by the solvent casting method. The formulated patches will be evaluated for physicochemical parameters including thickness, weight variation, folding endurance, moisture content, moisture uptake, tensile strength, drug content uniformity, surface pH, and percentage elongation. In vitro drug release and ex vivo skin permeation studies will be carried out using Franz diffusion cells. The anti-inflammatory potential will be assessed through suitable in vitro methods, while skin irritation studies will be performed to evaluate patch safety. The developed formulation is expected to provide controlled and sustained delivery of phytoconstituents, reduce dosing frequency, minimize systemic side effects, and improve therapeutic efficacy in rheumatoid arthritis. This study may contribute to the development of a safe, effective, and patient-friendly herbal transdermal drug delivery system and provide a scientific basis for the use of polyherbal formulations in the management of rheumatoid arthritis.
Keywords: Rheumatoid arthritis (RA); thickness; weight variation; folding endurance; moisture content; moisture uptake; tensile strength; drug content uniformity; surface pH